Pengembangan Media Kartu Interaktif Berbasis QR Code untuk Meningkatkan Kualitas Pembelajaran Pendidikan Agama Islam - ayu, Nazwanisa nimas (Maliki Interdisciplinary Journal, 2025)
Islamic Religious Education (IRE) faces challenges in delivering moral and spiritual values in ways that are engaging and aligned with the needs of today’s students. This study explores the use of an innovative medium called Interactive Cards as an effort to enhance the effectiveness and appeal of IRE learning. Using a qualitative descriptive method, the research examines the fundamental concept, implementation, and benefits offered by Interactive Cards in teaching and learning activities. This medium combines printed cards with QR code technology that directs students to video materials and is complemented by activities such as group discussions and presentations. The findings indicate that Interactive Cards can encourage student engagement, strengthen understanding of moral values, and foster 21st-century skills, including critical thinking, effective communication, and collaboration. Therefore, Interactive Cards are considered a relevant, contextual, and interactive innovation in developing more meaningful religious education.